Pairing Games and Markets - Ahmet Alkan; Alparslan Tuncay (Fondazione Eni Enrico Mattei (FEEM), 2014)
Pairing Games or Markets studied here are the non-two-sided NTU generalization of assignment games. We show that the Equilibrium Set is nonempty, that it is the set of stable allocations or the set of semistable allocations, and that it has several notable structural properties. We also introduce the solution concept of pseudostable allocations and show that they are in the Demand Bargaining Set. We give a dynamic Market Procedure that reaches the Equilibrium Set in a bounded number of steps. We use elementary tools of graph theory and a representation theorem obtained here.
Keywords: C71; C78; 330; Stable Matching; Competitive Equilibrium; Market Design; NTU Assignment Game; Roommate Problem; Coalition Formation; Bargaining Set; Bilateral Transaction; Gallai Edmonds Decomposition